2011
DOI: 10.1016/j.kjms.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Low‐power holmium:YAG laser urethrotomy for urethral stricture disease: Comparison of outcomes with the cold‐knife technique

Abstract: In this prospective randomized clinical trial, we aimed to evaluate the safety and efficacy of endourethrotomy with holmium:yttrium-aluminium-garnet (HO:YAG) laser and compare the outcomes with the conventional cold-knife urethrotomy. Fifty-one male patients with single, iatrogenic, annular strictures of the urethra were randomly divided into two groups; 21 patients who underwent direct-vision endoscopic urethrotomy with Ho:YAG laser (15 W; 1,200-1,400 mJ; 8-12 Hz) at 12 o'clock position (laser group) and 30 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 24 publications
8
41
0
2
Order By: Relevance
“…Recurrence rate Recurrence rate at 3, 6, and 12 months was evaluated in Atak et al [7] and Jabłonowski et al [9] studies, which had similar outcomes. At 3 months, the RR for recurrence was 0.55 (95% CI 0.18-1.66, p = 0.29), which favored the laser urethrotomy.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrence rate Recurrence rate at 3, 6, and 12 months was evaluated in Atak et al [7] and Jabłonowski et al [9] studies, which had similar outcomes. At 3 months, the RR for recurrence was 0.55 (95% CI 0.18-1.66, p = 0.29), which favored the laser urethrotomy.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Neither Atak et al [7] and Jabłonowski et al [9] nor Dutkiewicz and Wroblewski [10] reported complications during or after the procedure.…”
Section: Complicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…There have been a few prospective randomized clinical trials in the recent past on comparative study of Holmium laser over conventional cold knife for internal urethrotomy. In a study, done by Atak et al .,[15] 51 male patients with single, iatrogenic, annular strictures of the urethra were randomly divided into two groups; 21 patients underwent urethrotomy with Ho: YAG laser and 30 patients underwent direct vision urethrotomy with cold-knife. The results obtained were analyzed and compared at 3 months, 6 months, 9 months, and 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Laser types are Nd:YAG, argon and diode and Ho:YAG and KTP [7]. In a recent study, low-power holmium laser urethrotomy was compared with the cold knife technique [8]. The operative time of the laser group was shorter than that of the cold knife group (16.42 ± 8.04 vs. 23.83 ± 5.47 min; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%